Climatic niche lability but growth form conservatism in the African woody flora - (:unkn) unknown (My University, 2022)
Climatic niche evolution during the diversification of tropical plants has received little attention in Africa. To address this, we characterised the climatic niche of >4000 tropical African woody species, distinguishing two broad bioclimatic groups (forest vs. savanna) and six subgroups. We quantified niche conservatism versus lability at the genus level and for higher clades, using a molecular phylogeny of >800 genera. Although niche stasis at speciation is prevalent, numerous clades individually cover vast climatic spaces suggesting a general ease in transcending ecological limits, especially across bioclimatic subgroups. The forest biome was the main source of diversity, providing many lineages to savanna, but reverse shifts also occurred. We identified clades that diversified in savanna after shifts from forest. The forest-savanna transition was not consistently associated with a growth form change, though we found evolutionarily labile clades whose presence in forest or savanna is associated respectively with climbing or shrubby species diversification.
Keywords: African Research